An observational study of PM(10) and hospital admissions for acute exacerbations of chronic respiratory disease in Tasmania, Australia 1992–2002 - Mészáros, D (BMJ Open Respir Res, 2015)
OBJECTIVE: Particulate matter with a diameter below 10 µ (PM(10)) has been a major concern in the Tamar Valley, Launceston, where wood heaters are extensively used. We examined the relationship between PM(10) levels, meteorological variables, respiratory medications and hospital admissions for respiratory disease over the decade 1992–2002. METHODS: PM(10) levels were provided by the Department of Primary Industry Water, Parks and Environment, and meteorological variables from the Bureau of Meteorology. We obtained hospital discharge codes for the Launceston General Hospital. Poisson regression was used for statistical analyses. RESULTS: Mean daily PM(10) levels declined from 50.7 to 16.5 μg/m(3). Hospitalisations for asthma decreased from 29 to 21 per month, whereas chronic obstructive pulmonary disease (COPD) increased and bronchitis/bronchiolitis remained unchanged. We found a 10 μg/m(3) increase in PM(10) to be associated with a 4% increase in admissions for acute bronchitis/bronchiolitis (p0.05), but no association with asthma or COPD was found. All respiratory diseases showed seasonal patterns of hospitalisation. CONCLUSIONS: This is the first long-term study in Australia to demonstrate an association between PM(10) levels and respiratory diseases. Reducing exposure to PM(10) may decrease hospital admissions for respiratory diseases. IMPLICATION: Better preventive measures, including sustained public health initiatives to combat air pollution, are required to reduce respiratory morbidity.